Intimate Intrusions Revisited: A Case of Intimate Partner Abuse and Violations of the Territories of the Self - Allen-Collinson, Jacquelyn (Qualitative Sociology Review, 2009)
Intimate partner abuse is a complex, multi-faceted phenomenon, highly situated and “locally-produced” by intimate partners in the domestic interactional milieu. Adopting a symbolic interactionist approach, this article uses a limited topical life-history case study to investigate the interactional experiences of a male victim of female-perpetrated intimate partner abuse. The theoretical analysis utilises Goffman’s conceptualisation of the “territories of the self” and their subjection to various forms of contamination or “modalities of violation”, applied in this case to the contested domestic interactional milieu. The paper seeks to add to a developing qualitative literature on male victims’ experiences of intimate abuse and violence, and to extend Goffman’s conceptual insights into a new domain.